A revision of the family Syringogastridae (Diptera: Diopsoidea) - Marshall, S. A.; Buck, M.; Skevington, J. H.; Grimaldi, D. (Zootaxa, 2009)
The New World family Syringogastridae (Diptera, Acalyptratae) with the single genus Syringogaster is revised. Eleven new extant species are described in four newly recognized species groups to give a total of 20 extant species (S. brachypecta, S. apiculata and S. tenuipes in the rufa-group; S. atricalyx, S. figurata, S. plesioterga, and S. dactylopleura in the figurata-group; and S. nigrithorax, S. brunneina, S. sharkeyi and S. palenque in the brunnea-group; Marshall & Buck are the authors of all extant new species). The craigi-group includes two new fossil species, S. miocenecus Grimaldi and S. craigi Grimaldi, each described on the basis of a unique Miocene (ca. 17 myo) amber specimen from the Dominican Republic. Morphological and molecular characters are used to estimate phylogenetic relationships among species of Syringogastridae, and between Syringogastridae and related diopsids. The fossil species appear to form the sister group to the Central and South American figurata group, and reveal Antillean extinction of the family from earlier in the Tertiary.